2008
DOI: 10.1111/j.1469-0691.2008.01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organisation of the CTX element among toxigenic Vibrio cholerae isolates

Abstract: The composition and gene arrangement of the CTX genetic element were compared in 36 Vibrio cholerae isolates obtained during 2004-2006 from Iran. Long-PCR amplification of the CTX genetic element, using primers targeting ig1 and attB2, revealed three PCR products of c. 6.9, 5.6 and 2.6 kb, respectively. Southern blot hybridisation revealed that 30%, 17% and 53% of the isolates had one, two and three copies of the zot gene, respectively. PCR analysis of internal regions showed that isolates with three copies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…Vibrio cholerae O1 causes acute gastrointestinal disease, which is reported annually in Iran with differing frequency (Bakhshi et al, 2008). However, non-O1/non-O139 strains are not associated with epidemics, but several cases of sporadic diarrhoea, gastroenteritis and skin infections have been reported (Restrepo et al, 2006;Rozemeijer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio cholerae O1 causes acute gastrointestinal disease, which is reported annually in Iran with differing frequency (Bakhshi et al, 2008). However, non-O1/non-O139 strains are not associated with epidemics, but several cases of sporadic diarrhoea, gastroenteritis and skin infections have been reported (Restrepo et al, 2006;Rozemeijer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 94 clinical isolates of V. cholerae O1 El Tor obtained from different outbreaks between 2004 and 2009 were studied. A previous study in this laboratory showed that these isolates were Inaba and Ogawa serotypes (Bakhshi et al, 2008). In the present study, three strains were selected randomly, one from each of the three different arrangements of the CTX cassette.…”
Section: Methodsmentioning
confidence: 96%
“…The RS2 element is like RS1 but lacks the rstC ORF; thus, the CTX cassette contains only the rstA, rstB and rstR ORFs (Davis & Waldor, 2003). A previous report by this laboratory showed that, among V. cholerae isolates obtained from various parts of Iran, three distinct CTX cassettes with different arrangements existed (Bakhshi et al, 2008) (Fig. 1).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Vibrio cholerae is the causative agent of cholera; which can cause a considerable difficulties like diarrhea, dehydrates the body, acidosis, shock and ultimately death (2). The burden of this disease is well documented in the world and so far, seven global pandemic of cholera is reported (3,4). As many scientists from all over the world believe that many pathogenic bacteria have the quorum sensing system which is one of the major virulence factors (5).…”
Section: Introductionmentioning
confidence: 99%